Feature, Planning and Uses of Big Data: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the era of Computing Technology, data plays a role of lifeblood in various fields to make decisions. Without consistent and reliable data, the organizations cannot make decisions at right time. To design the data in an effective way, traditional methods were not proved to be effective because data is increasing from Kilo Bytes to Giga Bytes and then to Petta Bytes. Because of large diversity of data that is changing very rapidly and massively, big data is an emerging technology that takes an initiative to overcome these problems. In addition to the large volume of data, big data also handles varieties, velocity, veracity and value of data. Various tools being used to analyze the big data like Hadoop, MapReduce are also discussed in this paper. Architecture of Hadoop which is used to convert diverse and unstructured data into uniform and structured form is also described in this paper. Big data plays a significant role in various areas like banking, industries, E-Governance etc.